Karakteristik Pasien Terkonfirmasi Covid-19 Di Rsud Al-Mulk Kota Sukabumi Periode September 2020 - Juni 2021 - Lisna Agustiyah; Sudarto Ronoatmodjo (NERSMID : Jurnal Keperawatan dan Kebidanan, 2021)
Covid-19 is an infectious disease caused by the Sars-Cov-2 virus. Laboratory examinations have an important role to help diagnose Covid-19 disease. The simplest laboratory examination is a complete hematological examination to provide multiple prognostic that are useful for the clinical team in addition to other supporters, namely chest x-rays and clinical manifestations that occur in patients. Objective: This study aims to determine the results of laboratory examinations and to see the characteristic of Covid-19 confirmed patients treated at the Al-Mulk Hospital, Sukabumi City from September 2020 to June 2021. Methods This research is a descriptive analytic study. Total samples in this study were 80 patients who were confirmed as a Covid-19 patients through RT-PCR examination and performed a complete hematological examination at the beginning of the treatment period. Age is represented in median (range), demographic characteristics and other clinical manifestations are expressed in frequency and percentage. Research Results Based on the results of the study, the median age of patients was 52±10.96 years-old, and majority of confirmed covid-19 patients under treatment are women (61,3%). The levels of hemoglobin, leukocyte and platelets most of the patients had normal values but 67,5% patients had lymphopenia (67.5%). An increase in SGPT enzyme levels occurred in 76.95% of patients and an increase in Urea level only occurred in 14.10% of patients. The most common comorbid disease was diabetes (47.6%) while the symptoms commonly experienced by patients were cough (51.3%) and shortness of breath (41.3%) with a chest X-ray had bilateral pneumonia (66.2%). Most of the patients went home in good condition (62.6%) dan 5.0% of patients died during the treatment period.